2006
DOI: 10.1111/j.1365-2133.2006.07378.x
|View full text |Cite
|
Sign up to set email alerts
|

E6/E7 expression of human papillomavirus types in cutaneous squamous cell dysplasia and carcinoma in immunosuppressed organ transplant recipients

Abstract: Transcriptional activity of the E6/E7 oncogenes in AK and SCC suggests an active role of HPV in the lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
40
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 39 publications
4
40
0
2
Order By: Relevance
“…Both SCC and BCC develop mostly on sun-exposed sites (Frost & Green, 1994), and some specific types of HPV, including HPV-5, HPV-8, HPV-20 and HPV-77, have been shown to be activated by UV radiation (Akgül et al, 2005;Massimi et al, 2008;Michel et al, 2006;Purdie et al, 1999;Storey et al, 1998). Evidence of UV-induced E6/E7 oncogenicity and transcriptional activity of E6/E7 oncogenes in NMSC has been found (Al Moustafa et al, 2004;Dang et al, 2006;Michel et al, 2006). Furthermore, differences in transforming activity potential between various cutaneous HPV types have been shown, providing further evidence for a role of cutaneous HPV in the development of NMSC (Massimi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Both SCC and BCC develop mostly on sun-exposed sites (Frost & Green, 1994), and some specific types of HPV, including HPV-5, HPV-8, HPV-20 and HPV-77, have been shown to be activated by UV radiation (Akgül et al, 2005;Massimi et al, 2008;Michel et al, 2006;Purdie et al, 1999;Storey et al, 1998). Evidence of UV-induced E6/E7 oncogenicity and transcriptional activity of E6/E7 oncogenes in NMSC has been found (Al Moustafa et al, 2004;Dang et al, 2006;Michel et al, 2006). Furthermore, differences in transforming activity potential between various cutaneous HPV types have been shown, providing further evidence for a role of cutaneous HPV in the development of NMSC (Massimi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Expression of the early genes of betapapillomaviruses from the viral promoter in basal epidermal layers during natural infection in humans usually remains below the detection limits of in situ hybridization or real-time RT-PCR (Dang et al, 2006;Haller et al, 1995). This can explain the much slower and less efficient oncogenesis in man.…”
mentioning
confidence: 99%
“…Two recent studies have reported on antibodies against E6 and E7 proteins. 18,19 We report here the results of a pilot study of the relationship between antibodies against HPV-L1 antigens for 38 HPV types in relation to SCC in apparently immunocompetent patients with plasma collected before or after the diagnosis of their skin tumor. We used biological samples and data from the Oxford component of the European Prospective Investigation into Cancer and Nutrition (EPIC-Oxford).…”
mentioning
confidence: 99%